Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/20008198.2019.1672948
|View full text |Cite
|
Sign up to set email alerts
|

A decennial review of psychotraumatology: what did we learn and where are we going?

Abstract: On 6 December 2019 we start the 10th year of the European Journal of Psychotraumatogy (EJPT), a full Open Access journal on psychotrauma. This editorial is part of a special issue/ collection celebrating the 10 years anniversary of the journal where we will acknowledge some of our most impactful articles of the past decade (also discussed below and marked with * in the reference list). In this editorial the editors present a decennial review of the field addressing a range of topics that are core to both the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 249 publications
(259 reference statements)
2
60
0
1
Order By: Relevance
“…With a growing international movement towards more open science (Olff et al, 2019) and making data findable and re-usable, it is time for the traumatic stress field to fully recognize the value of preservation, sharing, and re-use of data. This recognition will have implications for our current and future research practices, and will shape the choices we make now regarding the legacy of past research.…”
Section: 在创伤应激研究中的数据保存 共享和重复使用mentioning
confidence: 99%
“…With a growing international movement towards more open science (Olff et al, 2019) and making data findable and re-usable, it is time for the traumatic stress field to fully recognize the value of preservation, sharing, and re-use of data. This recognition will have implications for our current and future research practices, and will shape the choices we make now regarding the legacy of past research.…”
Section: 在创伤应激研究中的数据保存 共享和重复使用mentioning
confidence: 99%
“…Withdrawal and real or expected negative responses from others relating to early experiences of bullying victimization may cultivate a vicious circle of shame and loneliness in these patients [40]. In addition, the neurobiology of social support is still poorly understood [11].…”
Section: Introductionmentioning
confidence: 99%
“…We present the results of the retrieved studies in terms of hypothalamic-pituitary-adrenal (HPA)-axis and endocannabinoid system function, immune reactions, neuroplasticity, novel pharmacological targets, and shortening of telomere length, which confirm a synergistic effect on a neurobiological level between the two entities.Brain Sci. 2020, 10, 173 2 of 15 studies have shown that trauma-related disorders are associated with the dysfunctioning of numerous biological systems, and that PTSD symptom severity exerts a cumulative effect on premature aging of the immune system and telomere length [8].Human functional imaging studies have identified an increased connectivity between the ventromedial prefrontal cortex (vmPFC), locus coeruleus (LC), hypothalamus, hippocampus, basolateral amygdala (BLA), and bed nucleus of the stria terminalis (BNST) in PTSD patients, while more subcortical areas like the periaqueductal gray area (PAG) and central amygdala (CeA) gradually become involved when the severity of a threatening stimulus becomes aggravated [9,10].Before the last decade, the predominant neurobiological model of PTSD concentrated on the pathway of fear conditioning involving mainly the amygdala system [11]. The preparations of the new DSM-5 broadened the criteria to include further emotionally dysregulated states like anger, guilt, shame, and symptoms of derealization and depersonalization, as well as altered self-and other-related conditions and deficits in social cognitions.…”
mentioning
confidence: 99%
See 2 more Smart Citations